Implementasi Metode Talaqqi Terhadap Kualitas Belajar Kitab Kuning Siswa Di Madrasah Al Qismul ‘Ali Al Washliyah Medan - Syahrizal Yusuf; Abdul Rahman (Pascasarjana Universitas Islam Negeri Sumatera Utara Medan, 2026)
This study examines the implementation of the talaqqi method in the learning of kitab kuning at Madrasah Al Qismul ‘Ali Al Washliyah Medan and its implications for students' learning quality. The analysis focuses on the stages of talaqqi, the dynamics of teacher-student interaction, and its impact on students' comprehension of classical Islamic texts. Findings indicate that talaqqi significantly enhances students' ability to read unvowelled Arabic texts, identify basic nahwu-sharaf structures, and understand contextual meanings within kitab kuning. Repetitive reading and direct correction enable students to quickly improve phonetic accuracy and grammatical precision, resulting in more accurate comprehension of the texts. The method also strengthens academic discipline through structured practice and muroja'ah. However, implementation challenges remain, including varying student abilities, limited instructional time, and insufficient learning media. Overall, talaqqi provides strong pedagogical contributions to the effectiveness of kitab kuning learning and improves students' learning quality, although further adjustments are needed to ensure more equitable outcomes.